Epidemiology and clinical features of toxicity following recreational use of synthetic cannabinoid receptor agonists: a report from the United Kingdom National Poisons Information Service. (2nd July 2016) - Waugh, Jennifer; Najafi, Javad; Hawkins, Leonard; Hill, Simon L.; Eddleston, Michael; Vale, J. Allister; Thompson, John P.; Thomas, Simon H. L.
Abstract: Context: Toxicity from the use of synthetic cannabinoid receptor agonists (SCRAs) has been encountered increasingly frequent in many countries.Objective: To characterise presentation rates, demographic profiles and reported clinical features for users of SCRAs referred by health professionals in the United Kingdom to the National Poisons Information Service (NPIS), to compare reported toxicity between commonly used branded products, and to examine the impact of legal control measures on enquiry numbers.Methods: NPIS telephone enquiry records were searched for SCRA-related terms for the 8-year period 1st January 2007 to 31st December 2014, consolidating multiple enquiries about the same case into a single record. Demographic data, reported exposure details, clinical features and poisoning severity were analysed, excluding cases where SCRA exposure was unlikely.Results: Enquiries to the NPIS were made concerning 510 individuals relating to probable SCRA use, with annual numbers increasing year on year. Most patients were male (80.8%) and <25 years old (65.1%). Common clinical features reported in the 433 (84.9%) patients reporting SCRA use without other substances included tachycardia ( n  = 73, 16.9%), reduced level of consciousness ( n  = 70, 16.2%), agitation or aggression ( n  = 45, 10.4%), vomiting ( n  = 30, 6.9%), dizziness ( n  = 26, 6.0%), confusion ( n = 21, 4.8%), mydriasis ( n  = 20, 4.6%) and hallucinations ( n  = 20, 4.6%). The Maximum Poisoning Severity Score (PSS) indicated severe toxicity in 36 cases (8.3%). Legal control of "second generation" SCRAs did not affect the rate of growth in enquiry numbers or the proportion with severe toxicity. The three most commonly reported products were "Black Mamba" ( n = 88, 20.3%), "Pandora's Box" ( n = 65, 15.0%) and "Clockwork Orange" ( n = 27, 6.2%). Neurological and general features were recorded more often with "Clockwork Orange" than for "Black Mamba" and "Pandora's Box", but moderate or severe toxicity was significantly less common after reported use of this product.Conclusions: Enquiries about SCRA-related toxicity have become increasingly frequent in the UK in spite of legal controls and commonly involve younger males. Differences in the patterns of toxicity associated with different branded preparations may occur, although further work with larger patient numbers is needed to confirm this.